Stability of Iron–Quercetin Complexes in Synthetic Wine under In Vitro Digestion Conditions. Issue 10 (2nd September 2014) - Escudero, Leticia B.; Fusari, Cecilia M.; Altamirano, Jorgelina C.; Camargo, Alejandra B.; Wuilloud, Rodolfo G.
Abstract Wine is a dietary source of polyphenolic compounds with reported health benefits when moderately consumed. Several of these compounds can associate with metals forming complexes. Therefore, this work was conducted to reach a better understanding of the nature and chemical stability of wine‐derived Fe3+–quercetin complexes in a digestion model. The stability of the complexes in a synthetic (simulated) wine was studied before and after in vitro gastric and intestinal digestions by high‐performance liquid chromatography (HPLC) with UV‐Vis detection. Metal determination was performed by atomic absorption spectrometry (ETAAS) to evaluate possible dissociation of complexes. During HPLC analysis all peaks eluted from the chromatographic column were collected, acidified, and analyzed by ETAAS. The results showed that complexes remain substantially stable after gastric digestion conditions, with recoveries of 84% to 90%. Although metal complexes were partially degraded during intestinal digestion, 41% to 45% of the Fe3+–quercetin complexes was recovered.